al-Ghazali’s parenting skills attributes model - Jamiah Manap,; Sidek Baba, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Parenting skills is the basis of effective education and human potential development in family. Early education which begins at home is like stonework more impressive and everlasting. This is then followed by continuous guidance during adolescent and adulthood from the parents. Meanwhile, Imam al-Ghazali is a Muslim scholar which also discusses certain aspects of parenting skills. His multidiscipline works range from the field of religion to education, psychology, spirituality and philosophy. Thus, al-Ghazali’s Parenting Skill’s Attributes Model was developed as a basis to understand parenting from al-Ghazali’s perspectives. The model encompassed four main element of Muslim parenting: knowledge and education, relationship with Allah, relationship with children and relationship with others. Each domain was interrelated in empowering and completing the challenging task of today’s parenting. In summary, effective parenting skills is a must in developing strong, beneficial and mindful generation. In the meantime, multiple approaches should be critically analysed to enrich the corpus of knowledge in this field.